Nutrients in Matoa for Health and Exercise Performance: A Literature Study - Mandosir, Yohanis Manfred; Prasetyo, Yudik; Suhartini, Bernadeta; Kristanto, Budi (PT FORMOSA CENDEKIA GLOBAL, 2025)
Matoa is an endemic plant in Indonesia that has great potential in the health sector. This study aims to examine the antioxidant potential of matoa through a narrative review approach. The literature search method was carried out on the Google Scholar and Research Gate databases with the keywords